Influence of heat treatment on the mechanical response of aluminum alloy-A392: supersaturation and aging effect - Bobba, Sujith; Mukkollu, Sambasiva Rao; Bandaru, Chennakesava Rao; Leman, Zulkiflle (Springer, 2025)
The influence of heat treatment on the microstructure and mechanical properties of A392, Al–Si alloy are investigated in the current research work. The heat treatment optimization was carried out in two steps: First was to maximize the supersaturation of Si in α-Al, followed by water quenching; however, the second step included the aging effect. Aluminum alloy (A392) cast samples were solutionized at 460, 480, and 500 °C for a time period of 2, 4, 6, and 8 h and then employed with water quenching process. Microstructural characteristics and mechanical properties of solutionized samples were studied. The solutionizing at 480 °C for 6 h, followed by quenching, showed better optimization and an increase in mechanical properties with maximum supersaturation of Si. The optimization of aging treatment was performed by applying solutionizing at 480 °C for 6 h, pursued by quenching and further aging at temperatures (160, 180, and 200 °C) for (6, 9, and 12 h). The microstructure analysis, tensile strength, elongation, hardness, and fracture surface of the tensile specimens were examined. The optimal aging cycle obtained was at a temperature of 180 °C for 9 h. The optimal heat treatment cycle (T6 condition) of A392 alloy was solutionizing at 480 °C for 6 h, accompanied by water quenching and further artificial aging at a temperature of 180 °C for 9 h. The optimal condition of heat treatment increases the mechanical properties; strength (UTS) increased to 192.4 MPa from 106 MPa as-cast condition, and the overall percentage elongation increased up to 62%. The hardness increased to 135 BHN from 65 BHN.